Hippocampal Programmed Cell Death after Status Epilepticus - Abi-Habib, Ralph J. (2003)
Summary:  Purpose: Status epilepticus (SE) can result in acute neuronal injury with subsequent long-term age-dependent behavioral and histologic sequelae. To investigate potential mechanisms that may underlie SE-related neuronal injury, we studied the occurrence of programmed cell death (PCD) in the hippocampus in the kainic acid (KA) model. Methods: In adult rats, KA-induced SE resulted in DNA fragmentation documented at 30 h after KA injection. Ceramide, a known mediator of PCD in multiple neural and nonneural tissues, increased at 2–3 h after KA intraperitoneal injection, and then decreased to control levels before increasing again from 12 to 30 h after injection. MK801 pretreatment prevented KA-induced increases in ceramide levels and DNA fragmentation, whether there was reduction in seizure severity or not (achieved with 5 mg/kg and 1 mg/kg of MK801, respectively). Results: Both ceramide increases and DNA fragmentation were observed after KA-induced SE in adult and in P35 rats. Ceramide did not increase after KA-induced SE in P7 pups, which also did not manifest any DNA fragmentation. Intrahippocampal injection of the active ceramide analogue C2-ceramide produced widespread DNA fragmentation, whereas the inactive ceramide analogue C2-dihydroceramide did not. Conclusions: Our data support the hypotheses that (a) N-methyl-d-aspartate–receptor activation results in ceramide increases and in DNA fragmentation; (b) ceramide is a mediator of PCD after SE; and (c) there are age-related differences in PCD and in the ceramide response after SE. Differences in the ceramide response could, potentially, be responsible for observed age-related differences in the response to SE.